2010
DOI: 10.1503/jpn.090073
|View full text |Cite
|
Sign up to set email alerts
|

Emotion brain alterations in anorexia nervosa: a candidate biological marker and implications for treatment

Abstract: 267Background: Identification of the biological markers of anorexia nervosa (AN) is crucial for the development of new treatments. We aimed to determine whether AN is associated with disturbances in the nonconscious neural processing of innate signals of emotion and whether these disturbances persist after weight gain. Methods: In a retest design, 28 adolescent females with AN were tested at first admission to hospital and again after they had gained weight. Matched healthy control participants were tested at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
7
19
2
Order By: Relevance
“…In fact, the observed reduced P300 response to negative emotional faces in patients with anorexia nervosa has been interpreted as possible evidence of decreased cognitive processing ability in respect of negative emotional faces, which could lead to social difficulties and, as a consequence, to the maintenance of eating disorders. 50 Some ERP findings are very consistent with previous neuroimaging results on patients with anorexia nervosa, reporting neural disturbances in response to stimuli that are relevant to the pathology (eg, stimuli like food exposure, different emotional situations, or body images) 51…”
Section: Discussionsupporting
confidence: 85%
“…In fact, the observed reduced P300 response to negative emotional faces in patients with anorexia nervosa has been interpreted as possible evidence of decreased cognitive processing ability in respect of negative emotional faces, which could lead to social difficulties and, as a consequence, to the maintenance of eating disorders. 50 Some ERP findings are very consistent with previous neuroimaging results on patients with anorexia nervosa, reporting neural disturbances in response to stimuli that are relevant to the pathology (eg, stimuli like food exposure, different emotional situations, or body images) 51…”
Section: Discussionsupporting
confidence: 85%
“…These findings provide support for the “hypervigilance” component of evidence-based theoretical models on anxiety disorders and the neural theory that attention is in fact deployed implicitly. Similar results are found in the processing of food pictures regardless of caloric content in EDs (Blechert, Feige, Joos, Zeeck, & Tuschen-Caffier, 2011) whereas the inverse pattern (decreased responding particularly in the temporo-occipital regions) is found in adolescents with AN in response to facial expressions of emotion (e.g., disgust, fear, sadness) (Hatch et al, 2010). …”
Section: Theoretical Modelssupporting
confidence: 63%
“…Also, an electroencephalography study showed that early neural responses to emotional faces are reduced in both ill and recovered patients (Hatch et al, 2010), supporting the notion that early and automatic processing of emotional stimuli are altered in AN. Similar decreased early neural responses to emotional faces have also been noted in patients with social anxiety disorder (Mueller et al, 2009).…”
Section: Discussionmentioning
confidence: 62%